2011
DOI: 10.1128/iai.01386-10
|View full text |Cite
|
Sign up to set email alerts
|

Murine Immune Response to a Chronic Staphylococcus aureus Biofilm Infection

Abstract: Staphylococcus aureus has reemerged as an important human pathogen in recent decades. Although many infections caused by this microbial species persist through a biofilm mode of growth, little is known about how the host's adaptive immune system responds to these biofilm infections. In this study, S. aureus cells adhered to pins in culture and were subsequently inserted into the tibiae of C57BL/6 mice, with an infecting dose of 2 ؋

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(133 citation statements)
references
References 48 publications
8
123
0
2
Order By: Relevance
“…Another important factor when translating mouse infection models to human disease is infectious dose. This is particularly relevant when considering the initial bacterial challenge to the immune system, especially since the number of organisms seeding a given site during human infection is usually lower than the high S. aureus inocula used in many mouse models (i.e., 10 5 to 10 7 CFU) (30,(44)(45)(46). For example, a high infectious dose is likely to elicit an immediate and robust proinflammatory response attributed to a greater bacterial biomass (mediated by lipoteichoic acids, peptidoglycan, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…Another important factor when translating mouse infection models to human disease is infectious dose. This is particularly relevant when considering the initial bacterial challenge to the immune system, especially since the number of organisms seeding a given site during human infection is usually lower than the high S. aureus inocula used in many mouse models (i.e., 10 5 to 10 7 CFU) (30,(44)(45)(46). For example, a high infectious dose is likely to elicit an immediate and robust proinflammatory response attributed to a greater bacterial biomass (mediated by lipoteichoic acids, peptidoglycan, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…There are a range of in vivo models that simulate chronic infections, such as surface wounds [75,76], subcutaneous wounds [77,78], implant-related (such as catheter, orthopaedic, and dental) [79][80][81][82][83], otitis media [84][85][86], and CF [87][88][89][90] to name but a few. As with all models, some are deemed more applicable than others.…”
Section: In Vivo Investigation Of Biofilmsmentioning
confidence: 99%
“…This suggests that formation of biofilms and creation of suitable microenvironments in the host through virulence factors are intricately related steps that constitute the colonization phase of an acute infection of V. cholerae, and their concomitant down-regulation at high density could possibly be an exit strategy of the pathogen. However, in a chronic infection of S. aureus in a mouse model Shirtliff and colleagues found that early and late stages of biofilms elicit distinct host responses (Prabhakara et al, 2011). While early stage biofilms triggered a Th1-mediated acute inflammatory response-possibly to create conducive tissue microenvironment for colonization -the old biofilms induced Th2-mediated humoral response that was ineffective on the pathogen -perhaps an immune evasive mechanism that facilitates the chronic survival (Prabhakara et al, 2011).…”
Section: Chronic Infections Bacterial Persistence and Biofilmsmentioning
confidence: 99%
“…However, in a chronic infection of S. aureus in a mouse model Shirtliff and colleagues found that early and late stages of biofilms elicit distinct host responses (Prabhakara et al, 2011). While early stage biofilms triggered a Th1-mediated acute inflammatory response-possibly to create conducive tissue microenvironment for colonization -the old biofilms induced Th2-mediated humoral response that was ineffective on the pathogen -perhaps an immune evasive mechanism that facilitates the chronic survival (Prabhakara et al, 2011).…”
Section: Chronic Infections Bacterial Persistence and Biofilmsmentioning
confidence: 99%